Green and Gold: Promoting Eco-Adventure and Cultural Tourism for Inclusive and Sustainable Growth - Oscar F. Picazo (Philippine Institute for Development Studies (PIDS), 2015)
This paper briefly reviews the literature on the emerging concept of eco-adventure and cultural tourism, dubbed "green and gold tourism," respectively. It provides the rationale for conducting such a study in the Philippines (why the concern for inclusivity and environmental sustainability in tourism). It then establishes the feasible scope of such study and lists illustrative activities of inclusive and sustainable green and gold tourism. It also identifies concerns and issues about green and gold tourism in APEC countries and in the Philippines. Finally, it classifies emerging good practices in this area, including volunteer travel, promotion of home stays, community-organized and -owned tourism activities, establishing nonmainstream tourist routes and destinations, and tourists' involvement in cultural preservation and eco-rehabilitation.
Keywords: 330; Philippines; eco-adventure tourism; cultural tourism; green tourism; gold tourism; inclusive tourism; sustainable tourism; nontraditional tourism